Comparison of Early T-Cell Precursor and Non-ETP Subtypes Among 122 Chinese Adults With Acute Lymphoblastic Leukemia - Zhang, Yi; Qian, Jie-Jing; Zhou, Yi-Le; Huang, Xin; Li, Jian-Hu; Li, Xue-Ying; Li, Chen-Ying; Wang, Huan-Ping; Lou, Yin-Jun; Meng, Hai-Tao; Yu, Wen-Juan; Tong, Hong-Yan; et al. (Frontiers in Oncology, 2020)
Background: Adult T-cell acute lymphoblastic leukemia (T-ALL) is a rare hematological malignancy, and significantly linked to poor outcomes. Early T-cell precursor (ETP) leukemia is a unique subtype of T-ALL. The aim of this study is to compare the differences between ETP and non-ETP ALLs in China. Methods: We retrospectively analyzed the records of 122 adult T-ALL patients diagnosed and treated at our center between Jan 2014 and Jun 2019. All the patients enrolled were categorized into ETP and non-ETP ALL by immunophenotype, and further statistical analysis about clinical data and prognostic factors were performed. Results: Among the 122 cases, the male-to-female ratio was 2.8:1, and the median age is 29 (range 16-82) years. Except for 10 patients with insufficient immunophenotyping results, 47.3%(53/112) are ETP and 52.7%(59/112) are non-ETP. Compared with non-ETP patients, ETP-ALL patients had lower WBC counts and LDH levels, while they were older, had higher PLT counts and fibrinogen levels (all p<0.05). The complete remission (CR) was achieved in 68.0%(83/122) patients, 64.2% and 76.3% in ETP and non-ETP respectively (p=0.160). Totally, 44.6% (37/83) patients were relapsed. Allogeneic stem-cell transplantation (allo-SCT) was successfully performed in 36.1%(44/122) patients, of which 79.5%(35/44) were in CR1. With a median follow-up of 9.1(range 0.5-70.3) months, the estimated 2-year OS and RFS rates for the cohort were 38.0±5.1% and 39.1±6.3%, respectively. In ETP group the 2-year OS rate was 40.7±8.2% and RFS rate was 47.2±10.7%, while in non-ETP group 2-year OS rate was 37.9±7.0% and RFS rate was 39.2±8.3% (both p>0.05). In the landmark analysis of CR1 patients who had a survival of more than 6 months, allo-SCT group had significantly better survival outcomes than chemotherapy group, and the 2-year OS rates and RFS rates were 80.1±7.3% vs 28.4±8.4%, and 68.9±8.8% vs 12.8±7.2%, respectively (both p<0.0001). Multivariate analysis suggests that allo-SCT acts as an independent prognostic factor for both OS and RFS. Conclusions: Our results revealed that ETP accounted for a high proportion of T-ALL in Chinese. There is no CR rates and prognosis differences between ETP and non-ETP. Allo-SCT in CR1 can significantly improve patients’ survival.